Penelusuran Makna Taqwa, Dzikr, Dan Falah ( Kajian Semantik Dengan Pendekatan Teori Toshihiko Izutsu ) - fatah, ahmad (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2018)
This study concern with a linguistic and semantic approach based on Thoshihiko Izutsu theory. The method of study is semantic analysis on Quranic word, it is taqwa, dzikr and falah . According Izutsu word on Quran have basic meaning and correlational meaning. Basic meaning is always exist on correlational meaning. Izutsu explain that semantic is an analitical study about keyword of languange. The purpose of this study is to reach worldview (weltanschauung) conceptually from the man that used language for speaking, thinking and translating about the worldview.Based on basic meaning and correlational meaning, taqwa classified three aspect. First, avoid from kufur with faith to Allah. Second, doing all of command from Allah and avoid all of Him prohibition. Third, avoid from all activities that make so far from Allah. It means that taqwa included of thinking, attitude and activities in many aspect of life.Basic meaning of dzikir is to remember. Based on study of Quranic semantic, meaning of dzikir correlated with two aspect. First, it is mean warning or remembrance. Second, it is mean a glory. Meaning of dzikir also correlated with the object of dzikir. The word of dzikir found on Quran about 280 words.The word of falah found on Quran about 41 words. The essences of falah is to reach happiness in the world and here after. Correlational meaning of falah is correlated with theological aspect, economical aspect and psycho-social aspect. So, to reach of happiness (falah) is with a completely understanding of that aspesct.